OR12-4 Adipocyte Subpopulations Mediate Obesity-Associated Inflammation in Adipose Tissues - Luong, Quyen (J Endocr Soc, 2019)
Recent studies have shown that heterogeneity among adipocytes exists even within a single white adipose tissue (WAT) depot. Our lab has uncovered developmentally distinct subpopulations of WAT adipocytes that are distinguished by the expression of these genes: Wilms’ Tumor 1 (Wt1) (Type 1), Transgelin (Tagln) (Type 2), and Myxovirus 1 (Mx1) (Type 3). Utilizing Cre transgenic mice, transcription of which is directed by the promoters of these marker genes, lineage tracing analysis showed that these three preadipocyte subpopulations independently gave rise to adipocytes in vivo, and differentially contribute to the adipose tissue depots. In high-fat diet induced obesity, Type 1 and Type 2 adipocytes are found roughly the same abundance in perigonadal adipose tissue, with only low numbers of Type 3 adipocytes observed. Macrophages, organized into crown like structures (CLS) around dead and dying adipocytes, are detected in the vicinity of Type 1 adipocytes derived from Wt1 positive lineage. The distributions of Type 1 adipocytes and of CLS were determined by Kernel density estimation, and found to be significantly overlapped. On the other hand, over 80% of CLS are found in direct contact with Type 2 adipocytes in the perigonadal adipose tissue. This finding indicates that diet-induced obesity preferentially causes increased death of Type 2 adipocytes compared to other adipocyte subtypes. Taken together, these data indicate that adipocyte subpopulations, at least in part, mediate the inflammatory response in adipose tissue.